The little exercise book of advertising. Vol I - LEPĂDATU, Ioana; SZAMBOLICS, Julia (Presa Universitară Clujeană, 2024)
The Little Exercise Book of Advertising offers theoretical concepts and practical exercises that students can use in their classes. Each chapter ends with creatively designed exercises that highlight that chapter’’s specific theory. This book includes tasks such as developing a buyer persona profile, formulating a creative brief, comprehending a media strategy, and understanding the importance of correct budgeting.